Primary and Secondary Negative Symptoms in Schizophrenia - Mosolov, Sergey N.; Yaltonskaya, Polina A. (Frontiers in Psychiatry, 2022)
The negative symptoms of schizophrenia include volitional (motivational) impairment manifesting in avolition, anhedonia and social withdrawal, and emotional disorders such as alogia and affective flattening. Negative symptoms worsen patients’ quality of life and functioning. From the diagnostic point of view, it is important to differentiate between primary negative symptoms, which are regarded as an integral dimension of schizophrenia, and secondary negative symptoms occurring as a result of positive symptoms, comorbid depression, side effects of antipsychotics, substance abuse or social isolation. If secondary negative symptoms overlap with primary negative symptoms, it can create a false clinical impression of worsening deficit symptoms and disease progression, which leads to the choice of incorrect therapeutic strategy with excessive dopamine blockers loading. Different longitudinal trajectories of primary and secondary negative symptoms in different schizophrenia stages are proposed as an important additional discriminating factor. This review and position paper focuses primarily on clinical aspects of negative symptoms in schizophrenia, their definition, phenomenology, factor structure and classification. It covers the historical and modern concepts of the paradigm of positive and negative symptoms in schizophrenia. as well as a detailed comparison of the assessment tools and psychometric tests used for evaluation of negative symptoms.